Occupational health and public health : lessons from the past , challenges for the future (Stockholm, 2006)
"About a hundred years ago occupational and environmental health became an increasingly urgent topic in Western societies. Today's perceptions and organisation for the prevention and treatment of occupational health problems are to a great extent historical products of a specific regime of work during the classical industrial era. For several reasons occupational health and safety became a field of its own involving medical and technical expertise, politicians, public administrations, trade unions and employers associations. Its roots, however are also to be found in the general history of public health. In the context of the evolving welfare state the two fields of occupational and of public health have developed as overlapping, though separately organised social and scientific concerns. The affinity of the histories of the two fields was the main reason for organising the conference Occupational Health and Public Health. Lessons from the Past - Challenges for the Future in Norrköping in southern Sweden in September 2001 with a view of casting light on their relations and to promote collaboration between the two. This book is a summary of the conference.